Assistance in Developing Role Play Videos to Improve Therapeutic Communication Skills of Nursing Students - Sudarsih, Sri; Santoso, Windu; Taqiuddin, Muhammad Hafidh (Sarana Ilmu Indonesia (salnesia), 2025)
While still students, nurses are required to possess advanced communication skills to build effective relationships with the individuals they serve and provide quality care. This program will be implemented with a participatory and interactive approach, consisting of several stages: preparation, implementation, evaluation, and reporting. As an effort to improve nursing students' therapeutic communication skills, the Community Service activity focused on creating role play videos. This activity was carried out through four core stages: preparation, implementation, evaluation, and reporting. The results of measuring therapeutic communication skills through observations of students during the role play video preparation showed that all 26 items were completed by students during the role play. The mentoring activity for creating experience-based therapeutic communication role play videos was effective in improving students' therapeutic communication skills. The process of creating scenarios, assigning roles, and conducting role plays provided a hands-on learning experience that enabled students to better understand the concept of therapeutic communication.